2016
DOI: 10.1111/jdv.13794
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL) 31 induces in cynomolgus monkeys a rapid and intense itch response that can be inhibited by an IL‐31 neutralizing antibody

Abstract: These results demonstrate that an IL-31 mAb can inhibit IL-31-mediated pruritus in vivo, and could be an effective therapy for pruritic skin conditions like AD where IL-31 upregulation may play a role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 32 publications
3
36
0
Order By: Relevance
“…19,24 While the eIL-5-CuMV TT vaccine targets the allergy-associated hyper-eosinophilia and thereby reduces the number of toxic cells potentially causing tissue damage of the skin, the eIL-31-CuMV TT vaccine rather targets the allergic itching caused by the underlying allergic immune response in the skin. Comparably to the mAb against IL-31, we suggest that the vaccine-induced anti-IL-31 antibodies mitigate the IL-31-mediated pruritus 40,41 and thus lowering the self-inflicted trauma caused by the horse scratching its skin. When comparing the clinical benefit of blocking IL-31 in horses with other species, we noticed a reduction of skin lesion severity in IBH-affected horses, which is in contrast to atopic dermatitis trials in dogs and humans that only showed reduction of pruritus whereas no improvement of eczema.…”
Section: Discussionmentioning
confidence: 88%
“…19,24 While the eIL-5-CuMV TT vaccine targets the allergy-associated hyper-eosinophilia and thereby reduces the number of toxic cells potentially causing tissue damage of the skin, the eIL-31-CuMV TT vaccine rather targets the allergic itching caused by the underlying allergic immune response in the skin. Comparably to the mAb against IL-31, we suggest that the vaccine-induced anti-IL-31 antibodies mitigate the IL-31-mediated pruritus 40,41 and thus lowering the self-inflicted trauma caused by the horse scratching its skin. When comparing the clinical benefit of blocking IL-31 in horses with other species, we noticed a reduction of skin lesion severity in IBH-affected horses, which is in contrast to atopic dermatitis trials in dogs and humans that only showed reduction of pruritus whereas no improvement of eczema.…”
Section: Discussionmentioning
confidence: 88%
“…Although further studies clarifying the mechanism of IL-31 axis in the itch sensation will be needed, blockade of IL-31 signalling can be considered clinically valuable for AD treatment. The recent study by, Lewis et al[22] on the inhibitory effect of antibody against IL-31 in a cynomolgus monkey scratching model also supports the importance of IL-31 axis.Our newly established monkey model of scratching clarified the systemic actions of IL-31 by distinguishing the pruritus effects from the dermatitis effects and also confirmed that a single subcutaneous injection of nemolizumab provides inhibitory action for up to 2 months. This long-lasting effect depends on nemolizumab's long half-life, which is mainly due to the low systemic expression of IL-31RA, but has also been achieved by optimizing the antibody structure to prolong the antipruritic activity.…”
mentioning
confidence: 70%
“…Species is a clear reason for the difference between the two sets of results, but another major difference between the two studies is the method of administration; that is, the distribution of IL-31 would be limited to IL-31. Interestingly, Lewis et al [22] recently reported that cyIL-31 administration elicited an immediate scratching response not only by intravenous and subcutaneous but also by intradermal injection. The late itch response may also be closely related to a cellular mechanism of IL-31 action, which we discuss below.…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of IL‐31, a member of the IL‐6 cytokine family, have been shown to be higher in patients with CSU than in healthy controls, but lower than patients with atopic dermatitis . IL‐31 promotes Th2 inflammation but has also been reported to induce itch by its interaction with specific IL‐31 receptors on sensory nerves . Although primarily secreted by Th2 lymphocytes, IL‐31 has also been reported to be released from human mast cells .…”
Section: Effects Of the Mast Cell On The Local Environmentmentioning
confidence: 99%
“…195 IL-31 promotes Th2 inflammation 196 but has also been reported to induce itch by its interaction with specific IL-31 receptors on sensory nerves. 197,198 Although primarily secreted by Th2 lymphocytes, 196 IL-31 has also been reported to be released from human mast cells. 199 For this reason we have recently investigated the potential role of this cytokine in causing itch in CSU.…”
Section: Cytokinesmentioning
confidence: 99%